Immunosuppressants in Behcet’s disease: a boon or a bane? - Modi, Krishna; Prajapati, Vipul; Shukla, Dhaiwat; Malhotra, Supriya D. (International Journal of Basic & Clinical Pharmacology, 2022)
Adalimumab is a disease-modifying antirheumatic drug and monoclonal antibody that works by antagonising tumour necrosis factor-alpha prescribed in many rheumatological conditions like Rheumatic arthritis, Ankylosing spondylitis and Behcet’s disease. Serious side effects with this drug include heart and liver failure, nervous and blood disorders, allergic and immune system reactions and opportunistic infections. A 27-year-old female patient, known case of Behcet’s disease presented to the hospital with complaints of fever, cough and breathlessness following administration of Adalimumab, six doses over three months. Chest X-ray and BAL-CBNAAT was suggestive of Tuberculosis. AKT was started and Adalimumab was suspended until patient recover.